Transcription factor programming of human ES cells generates functional neurons expressing both upper and deep layer cortical markers - Miskinyte, Giedre (PLoS One, 2018)
Human neurodegenerative disorders affect specific types of cortical neurons. Efficient protocols for the generation of such neurons for cell replacement, disease modeling and drug screening are highly warranted. Current methods for the production of cortical neurons from human embryonic stem (ES) cells are often time-consuming and inefficient, and the functional properties of the generated cells have been incompletely characterized. Here we have used transcription factor (TF) programming with the aim to induce rapid differentiation of human ES cells to layer-specific cortical neurons (hES-iNs). Three different combinations of TFs, NEUROGENIN 2 (NGN2) only, NGN2 plus Forebrain Embryonic Zinc Finger-Like Protein 2 (FEZF2), and NGN2 plus Special AT-Rich Sequence-Binding Protein 2 (SATB2), were delivered to human ES cells by lentiviral vectors. We observed only subtle differences between the TF combinations, which all gave rise to the formation of pyramidal-shaped cells, morphologically resembling adult human cortical neurons expressing cortical projection neuron (PN) markers and with mature electrophysiological properties. Using ex vivo transplantation to human organotypic cultures, we found that the hES-iNs could integrate into adult human cortical networks. We obtained no evidence that the hES-iNs had acquired a distinct cortical layer phenotype. Instead, our single-cell data showed that the hES-iNs, similar to fetal human cortical neurons, expressed both upper and deep layer cortical neuronal markers. Taken together, our findings provide evidence that TF programming can direct human ES cells towards cortical neurons but that the generated cells are transcriptionally profiled to generate both upper and deep layer cortical neurons. Therefore, most likely additional cues will be needed if these cells should adopt a specific cortical layer and area identity.